Exploring the principles of construct and content validity presented in the tests of the textbook english unlimited - Robayo, Lucimaver González; Avendaño, Alberto Ramírez (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Este estudio de investigación tiene como objetivo explorar cómo los principios de validez de contenido y de construcción estánpresentes en los exámenes propuestos por el texto guía usado en el nivel elemental en una universidad privada, la relación con lasmetas de aprendizaje con los estudiantes, así como la reacción y entendimiento de profesores y estudiantes en relación conestas dos clases de validez. En el proceso de recolección de información se usaron dos instrumentos: una encuesta a estudiantes y un cuestionario a profesores de inglés acerca de los exámenes suministrados por el libro de texto. Los resultados revelan quehay inconsistencia en la validez de contenido y en la validez de construcción, tales como tiempo, nivel de dificultad, y preparación, entre otros. En relación con el principio de validez de construcción, no hay  una relación directa entre las actividades propuestas para las clases, además los temas no se practican en la misma forma en que se evalúan en los exámenes.Palabras clave: validez de contenido, validez de construcción, pruebas, libros de texto, evaluación. AbstractThis research study aimed at exploring the principles of construct and content validity presented in the tests of the textbook English Unlimited in a private university, the relation with the students’ learning goals in an ESP course, as well as the teachers’ and students’ reactions and understanding of these two types of validity. In the process of collectingdata, two instruments were  administered: a survey for students and a questionnaire for English teachers in relation to the tests provided in the textbook. The findings reveal that there is a mismatch in both content and construct validity influenced by several factors that are characteristic of these two types of validity, such as timing, level of difficulty and rehearsal, among others. In relation to content validity, students and teachers displayed a low level of satisfaction for somereasons: the tests provided by the textbooks  do not fulfill their expectations related to their learning’s goals, there is a lack of contextualized activities, as well as lack of exposure to the English Language. On the other hand, in relation to construct validity, there is no correlation between the types of activities proposed for the class and the tests given to the students.Key words: content validity, construct validity, testing, textbooks, evaluation.